Combined extracts of Garcinia mangostana fruit rind and Cinnamomum tamala leaf supplementation enhances muscle strength and endurance in resistance trained males. Issue 1 (22nd October 2018) - Konda, Manikyeswara Rao; Alluri, Krishnaraju Venkata; Janardhanan, Prason Kumar; Trimurtulu, Golakoti; Sengupta, Krishanu
Abstract: Background: A proprietary composition GMCT contains extracts of two popular Asian herbs viz., Garcinia mangostana (GM) fruit rind and Cinnamomum tamala (CT) leaf. We systematically evaluated physical performance and muscle strength enhancing ability of GMCT in a preclinical mouse model followed by a 42-days double-blind placebo controlled human trial in resistance trained adult males. Methods: Four groups of Swiss albino mice (20–30 g body weight) ( n  = 6) were fed a standard laboratory diet and given Carboxymethylcellulose sodium (CMC), 150 mg/kg GMCT (GMCT-150), 300 mg/kg GMCT (GMCT-300) or 50 mg/kg Oxymetholone (OXY) via oral gavage for 21 days. On day 22, the animals' physical performance and muscle strength were assessed in a forced swimming test (FST) and forelimb grip strength experiment, respectively. In the human trial, thirty-eight resistance-trained young adults (mean age 26.32 ± 4.39 years, body weight 67.79 ± 12.84 kg, BMI 22.92 ± 3.54 kg/m 2 ) completed the trial. The participants received either GMCT ( n  = 19; 800 mg daily) or matched placebo (n = 19) for 42 days. As primary variables, 1-RM bench press, 1-RM leg press, and leg extension repetitions were measured at baseline and on days 14, 28 and 42 of the intervention. Anthropometric parameters and serum markers such as free testosterone, insulin-like growth factor 1 (IGF-1), insulin and lactate were also measured before and after the intervention. Results: GMCT-300 mice showed significant improvement in swimming time (GMCT: 395.3 ± 81.70 s vs. CMC: 271.6 ± 56.86 s; p  = 0.0166), distance (GMCT: 341.22 ± 65.88 m vs. CMC: 260.84 ± 49.15 m; p  = 0.0461) and grip strength (GMCT: 43.92 ± 6.97 N vs. CMC: 35.0 ± 6.92 N; p  = 0.0490), compared with the CMC group. At the end of the 42-day human trial, the per protocol analyses reveal that mean changes from baseline 1-RM bench press (GMCT: 23.47 ± 10.07 kg vs. PL: 3.42 ± 2.06 kg; p  < 0.0001), leg press (GMCT: 29.32 ± 16.17 kg vs. PL: 5.21 ± 1.72 kg; p < 0.0001), number of leg extension repetitions (GMCT: 6.58 ± 2.57 vs. PL: 2.05 ± 1.22; p < 0.0001) in GMCT group were significantly improved, compared with placebo. Intergroup difference analyses show that the changes from baseline left arm (GMCT: 1.09 ± 0.36 cm vs. PL: 0.68 ± 0.42 cm; p  = 0.0023), right arm (GMCT: 1.50 ± 0.44 cm vs. PL: 1.11 ± 0.43 cm; p  = 0.0088) circumference and lean mass (GMCT: 2.29 ± 2.09 kg vs. PL: 0.52 ± 2.58 kg; p  = 0.0404) in GMCT group were also significantly improved, compared with placebo. In comparison to placebo, GMCT supplementation did not improve free testosterone, IGF-1, insulin or lactate levels. Parameters of clinical biochemistry, hematology, urine and vital signs of the participants were within the normal range. Conclusion: GMCT supplementation is effective in increasing muscle strength, muscle size and, total lean mass, as well as endurance performance. Trial Registration. Clinical Trial Registry of India (CTRI/2015/01/005374), Registered on Jan 07, 2015; CTRI Website URL - http://ctri.nic.in